P-OGC73 Effect of pyloroplasty on the need for endoscopic intervention for delayed gastric emptying post oesophagectomy. (16th December 2021) - Chien, Siobhan; Khan, Khurram; Gall, Lewis; Craig, Carol; MacKay, Colin; Macdonald, Andrew; Forshaw, Matthew
Abstract: Background: Delayed gastric emptying (DGE) is a common complication following oesophagectomy, affecting 15-39% of patients. Controversy remains regarding the role of pyloric drainage procedures during oesophagectomy with gastric conduit reconstruction in reducing DGE. This study investigated the effect of pyloroplasty at the time of oesophagectomy on the need for endoscopic pyloric intervention post-operatively. Methods: We performed a retrospective analysis of all oesophagectomies performed in a single tertiary centre over a 10-year study period between 1 January 2010 and 31 December 2019. Electronic records were reviewed to analyse patient demographics, operative details and post-operative outcomes, as well as the need for endoscopic procedures after surgery. Patients were dichotomized into two groups, with those who had pyloroplasty performed at oesophagectomy compared to those who did not. Patients who died ≤30 days after oesophagectomy were excluded from analysis. Patients were followed up for a median of 32 months (IQR 19-60).  Results: 298 patients were eligible for the study, of whom 80/298 (26.8%) had a pyloroplasty performed. Demographics were evenly matched between the two groups. Patients undergoing Ivor-Lewis oesophagectomy were significantly more likely to have had pyloroplasty performed (90.0% vs. 24.3%; p < 0.001). Pyloroplasty had no significant effect on post-operative complication rates, ICU admission, need for re-operation or length of hospital stay. Patients without a pyloroplasty were significantly more likely to require endoscopic pyloric balloon dilatation (43.1% vs. 12.4%, p < 0.001) or pyloric botox injection (12.4% vs. 3.8%, p = 0.029) after oesophagectomy. Conclusions: In this study, patients who had a pyloroplasty at the time of oesophagectomy were significantly less likely to require endoscopic pyloric balloon dilatation and/or pyloric botox injection post-operatively. This has significant long-term implications for both patients' quality of life post-operatively and demands on over-stretched endoscopic services.